2011
DOI: 10.1136/gutjnl-2011-300755
|View full text |Cite
|
Sign up to set email alerts
|

Switch to adalimumab in patients with Crohn's disease controlled by maintenance infliximab: prospective randomised SWITCH trial

Abstract: Elective switching from infliximab to adalimumab is associated with loss of tolerance and loss of efficacy within 1 year. Adherence to the first anti-TNF agent is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 11 publications
2
82
0
5
Order By: Relevance
“…The abstracts and/or full texts of the 34 studies were retrieved, evaluated in detail and filtered according to the eligibility criteria. After this stage five studies were left for inclusion in the review [27][28][29][30][31]. A hand search of the references of relevant citations resulted in an additional study being included in the final review [32].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The abstracts and/or full texts of the 34 studies were retrieved, evaluated in detail and filtered according to the eligibility criteria. After this stage five studies were left for inclusion in the review [27][28][29][30][31]. A hand search of the references of relevant citations resulted in an additional study being included in the final review [32].…”
Section: Search Resultsmentioning
confidence: 99%
“…The majority (4/6) of the studies concluded that patients had demonstrated a preference for SC drug administration [27][28][29][30] proportions ranged from 44%-91%. Only one study reported that patients preferred IV drug delivery [32] and another found no difference in patient preference for either method [31].…”
Section: Patient Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may result in poor specificity, sensitivity and reproducibility. In this study, we determined the correlation between academically developed assays (Leuven and Amsterdam) that were used in several studies to detect IFX drug levels and anti-IFX antibodies [17][18][19] and are routinely applied in patient diagnostics, and a commercially available assay (further referred to as BMD ELISA) used in the study of Pariente et al A total of 62 samples were analysed by all three institutes. Thirty six samples were clinical samples from patients containing different concentrations of IFX and ATI.…”
Section: Introductionmentioning
confidence: 99%
“…Ugyanígy elektív váltás remiszszióban lévő betegekben szintén nem javasolt, amint azt egy nemrégiben megjelent tanulmány adatai is bizonyít-ják. Ebben a tanulmányban IFX fenntartó kezeléssel remisszióban lévő betegekben a váltást követő évben csaknem háromszor gyakrabban (ADA váltás: 47% vs IFX folytatása: 16%) volt szükség dózisemelésre vagy a terápia felfüggesztésére szekunder hatásvesztés miatt [63].…”
Section: Megbeszélés éS Következtetésekunclassified